Risk analysis in geological CO2 storage projects - Rodríguez Dono, Alfonso (2008)
One of the causes of climate change is the anthropogenic emission of greenhouse gases, mainly CO2. To reduce these emissions one of the options that exist is the geological storage of CO2. This thesis sets out the criteria for selecting suitable sites for the geological storage of CO2, as well as its associated costs and risks, and finally, an analysis of these risks, for which specific methodologies for analyzing risks for geological CO2 storage projects.